2018
DOI: 10.3390/en11051298
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Injector Hole Diameter on Spray Behaviour for Butanol-Diesel Blends

Abstract: Optimising the combustion process in compression ignition (CI) engines is of interest in current research as a potential means to reduce fuel consumption and emission levels. Combustion optimisation can be achieved as a result of understanding the relationship between spraying technique and combustion characteristics. Understanding macroscopic characteristics of spray is an important step in predicting combustion behaviour. This study investigates the impact of injector hole diameter on macroscopic spray chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…The spray test was conducted at atmospheric condition. The setup was consistent with those described in previous work [4,16,20]. Figure 2 shows a schematic diagram of the spray setup system.…”
Section: Spray Test Setupsupporting
confidence: 60%
See 1 more Smart Citation
“…The spray test was conducted at atmospheric condition. The setup was consistent with those described in previous work [4,16,20]. Figure 2 shows a schematic diagram of the spray setup system.…”
Section: Spray Test Setupsupporting
confidence: 60%
“…ABE (10%) was also blended with 90% neat diesel (D) creating ABE10D90. Blend density was measured according to ASTM 1298 [20,21]. The blends' dynamic viscosities were measured according to the ASTM 445-01 [22] using a Brookfield Viscometer (DV-II+Pro Extra, AMETEK Brookfield, Middleboro, MA, USA).…”
Section: Fuel Preparationmentioning
confidence: 99%
“…Shuai et al [42] found that advanced injection provided reduced soot, HC, and CO pollutants and higher NOx than the retarded injection. Algayyim et al [43] investigated the influence of injector hole diameter on macroscopic spray behavior of butanol-diesel blends. They concluded that efficient diesel engine performance can be attained by controlling injection attributes.…”
Section: Introductionmentioning
confidence: 99%
“…The spray formation, considered as a fuel parameter, depends mainly, at a selected temperature, on viscosity, surface tension, low boiling temperature, and volatility of fuel [35]. However, the spray formation, considered on the engine hardware side, depends on injection pressure, injection vessel diameter, and chamber parameters [36,37]. Meanwhile, the core findings of diesel fuel quality sensor development that is based on a capillary optrode are characterized by a set of interesting features:A capillary sensor with a principle of operation close to the measurement of fuel injection parameters enables time of examinations below a few minutes [38].…”
Section: Introductionmentioning
confidence: 99%